Regulation measures for ensuring financial stability of the organizations in Russia - I. V. Gladkov (Путеводитель предпринимателя, 2020)
Strengthening of a financial condition of the organizations is important for the economy development of Russia, however the number of bankrupt legal entities increases as in some branches, and regions of our country. Search of new financial instruments is necessary for financial improvement of the industrial enterprises, credit institutions.